1995
DOI: 10.1115/1.2847815
|View full text |Cite
|
Sign up to set email alerts
|

Exergy Analysis of a Solar Heating System

Abstract: Exergy destruction associated with the operation of a solar heating system is evaluated numerically via an exergy cascade. As expected, exergy destruction is dominated by heat transfer across temperature differences. An energy analysis is also given for comparison of exergy cascade to energy cascade. Efficiencies based on both the first law and second law of thermodynamics are calculated for a number of components and for the system. The results show that high first-law efficiency does not mean high second-law… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Besides this, it is essential to optimize the solar system design and its operation. The solar air heating system has been studied comprehensively, considering different pivotal parameters such as their exergy, exergetic efficiency, and entropy generation …”
Section: Introductionmentioning
confidence: 99%
“…Besides this, it is essential to optimize the solar system design and its operation. The solar air heating system has been studied comprehensively, considering different pivotal parameters such as their exergy, exergetic efficiency, and entropy generation …”
Section: Introductionmentioning
confidence: 99%
“…Solar collectors have been examined in terms of their exergy, exergy efficiency, and entropy generation [4][5][6]. Bejan et al conducted an exergy analysis of a solar collector and found that the amount of exergy delivered by solar collector systems is affected by heat transfer irreversibilities [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the energy equalizing does not consider many internal and conversion losses factors. High thermal effectiveness does not maintain the operation high performance [15]. The article [13] presents the theoretical model of the flat solar collectors' energy and exergy analyses, through which we can study the influence of all designed parameters at the operating characteristics.…”
Section: Introductionmentioning
confidence: 99%